2022
DOI: 10.1021/acs.iecr.2c00667
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Glycerol Carbonate via Alcoholysis of Urea with Glycerol: Current Status and Future Prospects

Abstract: Glycerol carbonate is an important chemical in industrial chemistry. It could be synthesized from glycerol, which is a byproduct in the biodiesel production process. Alcoholysis of urea with glycerol is a promising approach for the synthesis of glycerol carbonate. Catalysts are indispensable for the reaction of alcoholysis of urea with glycerol. Summarizing the developed catalysts and unraveling the reaction mechanisms pave pathways to the rational design of better catalysts in the future. In this paper, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…According to Yuqiao Li et al [ 1 ] Zn possesses the capability of activating glycerol through the formation of Zn–GC, making Zn‐based catalysts suitable for the alcoholysis reaction of urea with glycerol. In the reaction, the Lewis acid sites of Zn 2+ can coordinate with the Lewis basic carboxyl group in the urea molecule, thereby facilitating the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Yuqiao Li et al [ 1 ] Zn possesses the capability of activating glycerol through the formation of Zn–GC, making Zn‐based catalysts suitable for the alcoholysis reaction of urea with glycerol. In the reaction, the Lewis acid sites of Zn 2+ can coordinate with the Lewis basic carboxyl group in the urea molecule, thereby facilitating the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, spinel compounds of the AB 2 O 4 are widely used as catalysts for numerous gas conversion processes, [9] applications in magnetic storage, satellite communications and information display technology, [10] anode materials for electrochemical energy storage, [11] and catalytic conversion of crude glycerol into high-value products. [1] Our previous studies on Zn-based catalysts reported that the calcination temperature affected the formation of spinel ZnAl 2 O 4 structures and DOI: 10.1002/sstr.202300337 ZnAl 2 O 4 is a cubic close-packed oxide with tetrahedral and octahedral sites in the lattice structure. The catalytic activity of ZnAl 2 O 4 is strongly connected with the surface properties caused by the partially inverse spinel ZnAl 2 O 4 structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations